Complement C1q expression in Erythema nodosum leprosum. - Edessa Negera; Stephen L Walker; Tsehaynesh Lema; Abraham Aseffa; Diana N Lockwood; Hazel M Dockrell (Public Library of Science (PLoS), 2018)
Complement C1q is a soluble protein capable of initiating components of the classical pathway in host defence system. In earlier qualitative studies, C1q has been implicated in the pathogenesis of Erythema Nodosum Leprosum (ENL). However, little is known about the role of this complement in ENL reaction. In the present study we described the protein level of C1q production and its gene expression in the peripheral blood and skin biopsies in patients with ENL reaction and lepromatous leprosy (LL) patient controls before and after treatment. Thirty untreated patients with ENL reaction and 30 non-reactional LL patient controls were recruited at ALERT Hospital, Ethiopia. Peripheral blood and skin biopsies were obtained from each patient before and after treatment. The level of circulating C1q in the plasma was determined by enzyme-linked immunosorbent assay. The mRNA expression of the three C1q components, C1qA, C1qB, and C1qC in the peripheral blood and skin biopsies was determined by qPCR. Circulating C1q in the peripheral blood of untreated ENL patients was significantly decreased compared to LL patient controls. Untreated ENL patients had increased C1q gene expression in the peripheral blood compared to LL controls. Similarly, C1qA and C1qC gene expression were substantially increased in the skin biopsies of untreated ENL patients compared to LL controls. However, after treatment none of these genes show significant difference in both groups. In conclusion, while circulating C1q is inversely correlated with active ENL reactions, its gene expression is directly correlated with ENL. The decreased circulating C1q may suggest the utilization of C1q in immune-complex formation in these patients. Therefore, C1q could be a potential diagnostic marker for active ENL reactions as well as for monitoring ENL treatment.